SARS-CoV-2 transmission risk from asymptomatic carriers: Results from a mass screening programme in Luxembourg - Paul Wilmes; Jacques Zimmer; Jasmin Schulz; Frank Glod; Lisa Veiber; Laurent Mombaerts; Bruno Rodrigues; Atte Aalto; Jessica Pastore; Chantal J. Snoeck; Markus Ollert; Guy Fagherazzi; et al. (The Lancet Regional Health. Europe, 2021)
Background: To accompany the lifting of COVID-19 lockdown measures, Luxembourg implemented a mass screening (MS) programme. The first phase coincided with an early summer epidemic wave in 2020. Methods: rRT-PCR-based screening for SARS-CoV-2 was performed by pooling of samples. The infrastructure allowed the testing of the entire resident and cross-border worker populations. The strategy relied on social connectivity within different activity sectors. Invitation frequencies were tactically increased in sectors and regions with higher prevalence. The results were analysed alongside contact tracing data. Findings: The voluntary programme covered 49% of the resident and 22% of the cross-border worker populations. It identified 850 index cases with an additional 249 cases from contact tracing. Over-representation was observed in the services, hospitality and construction sectors alongside regional differences. Asymptomatic cases had a significant but lower secondary attack rate when compared to symptomatic individuals. Based on simulations using an agent-based SEIR model, the total number of expected cases would have been 42·9% (90% CI [-0·3, 96·7]) higher without MS. Mandatory participation would have resulted in a further difference of 39·7% [19·6, 59·2]. Interpretation: Strategic and tactical MS allows the suppression of epidemic dynamics. Asymptomatic carriers represent a significant risk for transmission. Containment of future outbreaks will depend on early testing in sectors and regions. Higher participation rates must be assured through targeted incentivisation and recurrent invitation. Funding: This project was funded by the Luxembourg Ministries of Higher Education and Research, and Health.